2004
DOI: 10.1530/eje.0.1510173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic administration of PPAR-gamma ligand rosiglitazone in Cushing's disease

Abstract: Objective: Rosiglitazone, a thiazolidinedione compound with peroxisome proliferator-activated receptor-g (PPAR-g)-binding affinity, is able to suppress adrenocorticotropic hormone (ACTH) secretion in treated mice and in AtT20 pituitary tumor cells. These observations suggested that thiazolidinediones may be effective as therapy for Cushing's disease (CD). Patients and methods: Rosiglitazone (8 mg/day) was administered to 14 patients with active CD (13 women, one man, 18-68 years). Plasma ACTH, serum cortisol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 16 publications
(15 reference statements)
8
66
1
2
Order By: Relevance
“…Pioglitazone may have a potential negative effect on heart and bone (46). Thiazolidinediones have been demonstrated to have a direct adrenocorticotropic hormone (ACTH)-lowering effect on corticotrophinomas in vitro, but no convincing results arose from clinical trials on patients with CD (47). GLP1 analogues and dipeptidyl peptidase four inhibitors could be helpful in the management of GC-induced diabetes, increasing glucose dependent insulin secretion and reducing glucagon secretion as well as having positive effects on b-cell mass and function, appetite, adipocyte modulation, fat distribution, hyperlipidaemia, heart and bone (48,49).…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 99%
“…Pioglitazone may have a potential negative effect on heart and bone (46). Thiazolidinediones have been demonstrated to have a direct adrenocorticotropic hormone (ACTH)-lowering effect on corticotrophinomas in vitro, but no convincing results arose from clinical trials on patients with CD (47). GLP1 analogues and dipeptidyl peptidase four inhibitors could be helpful in the management of GC-induced diabetes, increasing glucose dependent insulin secretion and reducing glucagon secretion as well as having positive effects on b-cell mass and function, appetite, adipocyte modulation, fat distribution, hyperlipidaemia, heart and bone (48,49).…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 99%
“…Although initial studies showed that high dosages of the thiazolidinediones were able to inhibit tumor growth and ACTH and corticosterone levels in mice (Heaney et al 2002), the results of thiazolidinedione treatment in patients with CD and Nelson's syndrome (NS) have been rather disappointing (Ambrosi et al 2004, Suri & Weiss 2005, Mullan et al 2006, Pecori Giraldi et al 2006, Munir et al 2007, Kreutzer et al 2009). Therefore, PPARg agonists do not play a role in the medical treatment of CD.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
“…Um terceira opção no tratamento da sín-drome de Nelson seria o ácido trans-retinóico (ATRA), já que a administração dessa droga impede o crescimento de tumor corticotrofo implantado em subcutâneo de ratos (35). Outra possibilidade seria o uso de agonistas do PPARγ, porque estudos em animais demonstraram que a administração de rosiglitasona inibe a secreção de ACTH pelo corticotrofinoma, e o crescimento desses tumores (36) e estudo clínico, que avaliou a resposta de 14 pacientes com doença de Cushing à administração dessa droga na dose de 8 mg/dia, mostrou normalização do cortisol urinário em 42% dos pacientes (37). A ciproeptadina, antagonista serotoninérgico, também pode influenciar negativamente a produção de ACTH, por ação hipotalâmi-ca ou hipofisária (38), mas estudos em pacientes portadores de síndrome de Nelson não constataram eficácia da medicação no tratamento desta doença (39).…”
Section: Tratamento Medicamentoso Da Síndrome De Nelson: Flávia Moretunclassified